PEMAKNAAN TRADISI PETIK LAUT BAGI MASYARKAT PESISIR - Irma Juliana; Nindi Laili Safitri; Wulan Fadillah (Institut Nalanda, 2023)
Indonesia has very diverse traditions and customs. The culture in Indonesia is one of the historical heritages that we must preserve today because life is becoming more modern, little by little eroding the existence of local culture. In its history, Indonesia is a society with many tribes and cultures that have local wisdom that is preserved by the people. Petik Laut is one of the traditions in Indonesia which is currently still being carried out precisely in Puger District, Jember Regency. Puger people think that the results of the natural surroundings are a resource and the key to their well-being. Therefore, this has made some people who live in coastal areas have a tradition that is carried out as a form of gratitude and thanks because the natural resources they get from the sea can meet their needs. Coastal communities usually use rituals that have become a hereditary tradition as an expression of gratitude. In addition, this tradition carried out by coastal communities is also a prayer or hope that the fish catch will be abundant and also get safety. This activity is carried out during Muharram or Suro. This Petik Laut tradition is an amalgamation of local wisdom and religion. In the tradition of sea cucumbers, there are prayers and recitation of the holy verses of the Koran before finally the offerings are thrown into the sea